2022
DOI: 10.1177/09636897211051743
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Clinical Amelioration of Bone Fractures with Mesenchymal Stromal Cells: a Systematic Review and Meta-Analysis

Abstract: Even though reunion of bone fracture confronts clinicians, mesenchymal stromal cells (MSCs) are investigated to be curative in bone fracture. This study aimed to explore the application potential of MSCs for healing bone fractures. By inputting search terms and retrieving studies published up to March 2021, multiple databases, including PubMed, EMBASE, Web of Science, and Cochrane Library, were searched to identify eligible studies. The mean difference (MD) and 95% confidence interval (95% CI) were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…However, no studies with patients have assessed the effect of these growth factors on fracture-healing speed. The available clinical studies on the amelioration of fracturehealing by MSCs in patients (not specifically focusing on healing acceleration) were summarized in a systematic review and metaanalysis by Yi et al (95), which revealed no decrease in healing time in the MSC group. The included studies with human patients differed largely in their patient collectives and modes of MSC application (96)(97)(98)(99).…”
Section: Growth Factorsmentioning
confidence: 99%
“…However, no studies with patients have assessed the effect of these growth factors on fracture-healing speed. The available clinical studies on the amelioration of fracturehealing by MSCs in patients (not specifically focusing on healing acceleration) were summarized in a systematic review and metaanalysis by Yi et al (95), which revealed no decrease in healing time in the MSC group. The included studies with human patients differed largely in their patient collectives and modes of MSC application (96)(97)(98)(99).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Similarly, the study of Yi et al showed encouraging results from the use of MSCs in fractures, both in animal and human studies. Although the study assesses the administration of stem cells alone, their application seems to be effective in the treatment of bone fractures [ 27 ].…”
Section: Introductionmentioning
confidence: 99%